2016
DOI: 10.1016/j.paid.2016.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Leader emotional intelligence and subordinate job satisfaction: A meta-analysis of main, mediator, and moderator effects

Abstract: S. (2016). Leader emotional intelligence and subordinate job satisfaction: A meta-analysis of main, mediator, and moderator effects. Personality and Individual Differences, 102, 13-24. http://dx.doi.org/10.1016Differences, 102, 13-24. http://dx.doi.org/10. /j.paid.2016 LEADER EMOTIONAL INTELLIGENCE 2 ABSTRACTBased on a meta-analysis, leaders' emotional intelligence (EI) positively relates to subordinates' job satisfaction (̂ = .308). All three EI streams (ability, self-report, mixed) exhibit significant increm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
1
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 88 publications
(54 reference statements)
7
166
1
14
Order By: Relevance
“…A substantial body of research has demonstrated that trait EI is essential and important for job-related well being (Zampetakis and Moustakis, 2010;Fu, 2014;Schutte and Loi, 2014;Petrides et al, 2016;Clarke and Mahadi, 2017;Sun et al, 2017). Moreover, a meta-analysis study revealed that EI was positively correlated with job satisfaction (Miao et al, 2016(Miao et al, , 2017. Prior studies have demonstrated that the positive influence of EI on job satisfaction is well proven; however, the deeper mechanism of this association is unclear.…”
Section: Trait Emotional Intelligence and Job Satisfactionmentioning
confidence: 99%
“…A substantial body of research has demonstrated that trait EI is essential and important for job-related well being (Zampetakis and Moustakis, 2010;Fu, 2014;Schutte and Loi, 2014;Petrides et al, 2016;Clarke and Mahadi, 2017;Sun et al, 2017). Moreover, a meta-analysis study revealed that EI was positively correlated with job satisfaction (Miao et al, 2016(Miao et al, , 2017. Prior studies have demonstrated that the positive influence of EI on job satisfaction is well proven; however, the deeper mechanism of this association is unclear.…”
Section: Trait Emotional Intelligence and Job Satisfactionmentioning
confidence: 99%
“…Note. (C) Ceri-Booms, Curşeu, and Oerlemans (2017), the statistic is the population estimate corrected for attenuation due to measurement error, sampling error variance; (H) Harms and Crede (2010), the statistic is the estimated true score correlation; (M) Miao, Humphrey, and Qian (2016), the statistic is the corrected sample-sizeweighted mean correlation; (S) Schlaerth, Ensari, and Christian (2013) Additionally, the research illustrated that leader self-reported ratings are moderately positively correlated with contingent reward and the 5 I's of the full range model of leadership (ES ranged from .24 to .45). Most noteworthy is the strong positive finding between leader self-reported ratings and the behavioral facet of transformational leadership (ES = .56).…”
Section: Research On Leader Emotional Intelligencementioning
confidence: 99%
“…Kepuasan kerja adalah hasil dari persepsi (Sargent & Hannum, 2005) dan sikap yang dimiliki oleh seorang karyawan terkait dengan pekerjaannya (Rao & Sridhar, Schleicher et al, kepuasan kerja merupakan hal penting yang dapat membangun psikologi organisasi sehingga akan mempengaruhi perilaku organisasi (Miao, Humphrey, & Qian, 2016).…”
Section: Kepuasan Kerjaunclassified